Administration of biphosphonates as an adjuvant therapy in breast cancer patients - J. Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2002)
The development of bone metastases in patients with breast cancer depends on tumor-induced ostaoclastic resorption of bone. It is associated with severe bone pain, fractures and hypercalcaemia and simultaneously decreases the overall survival of patients. Micrometastases within bone marrow of breast cancer patients may be often found even if there are no signs of metastases in lymph nodes. Treatment of breast cancer patients with biphosphonates is associated with reduced frequency of skeletal complications. Biphosphonates not only inhibit the osteolitic functions of osteoclast at the site of bone metastases but also reduce the local concentration of different growth factors such as TGF-ß or IGF-1. Biphosphonates can also directly influence the growth of caner cells by inducing their apoptosis. Results of a recently published trial which accrued 1 069 breast cancer patients demonstrate that clodronate during the total follow-up period of 5 years, significantly improved the overall survival. Clodronate may also reduce the occurrence of bone metastases in breast cancer patients, but this reduction is significant only during the medication period (2 years). Low costs of clodronate and the lack of any severe side effects make the administration of biphosphonates a promising strategy as an adjuvant to a standard breast cancer patients treatment.